Peanut skin extract mediated synthesis of gold nanoparticles, silver nanoparticles and gold–silver bionanocomposites for electrochemical Sudan IV sensing. Issue 6 (1st December 2016) - Pani, Alok; Thanh, Tran Duy; Kim, Nam Hoon; Lee, Joong Hee; Yun, Soon‐Il
Abstract : Sustainable methods are needed for rapid and efficient detection of environmental and food pollutants. The Sudan group of dyes has been used extensively as adulterants in food and also are found to be polluting the soil and water bodies. There have been several methods for detection of Sudan dyes, but most of them are not practical enough for common use. In this study, the electrochemical detection efficiency and stability of gold nanoparticle (AuNPs), silver NPs and Au–Ag bionanocomposites, synthesised by peanut skin extract, modified glassy carbon electrode has been investigated. The synthesised nanomaterial samples were characterised, for their quality and quantity, using ultra–visible spectroscopy, inductive coupled plasma mass spectrophotometer, Fourier transform infrared spectroscopy, energy‐dispersive X‐ray spectroscopy, high‐resolution transmission electron microscope and field emission scanning electron microscope. The nanomaterial hybrid electrodes showed great efficiency and stability in the detection of Sudan IV compared with the other previous electrodes. The peak current of the Sudan IV oxidation and reduction was found to be proportional to its concentration, in the range of 10–80 µM, with a detection limit of 4 µM. The hybrid electrodes showed 90% stability in detection for 20 cycles.